Psychopathological Processes Involved in Social Comparison, Depression, and Envy on Facebook - Pera, Aurel (Frontiers in Psychology, 2018)
Is Facebook utilization beneficial or detrimental for psychological well-being? I draw on outstanding research (e.g. Chou and Edge, 2012; Lin and Utz, 2015; Appel et al., 2016; Ehrenreich and Underwood, 2016; Vogel and Rose, 2016; and Hu et al., 2017) to substantiate that examining other individuals’ positively presented material on Facebook may have detrimental consequences. Increasing comparisons on Facebook may generate feelings of envy, the latter being a significant process determining the effect of growing social comparison on psychological well-being. To date, there is an increasing body of literature investigating the psychological consequences of Facebook usage, the function of relationship closeness in producing the feelings of contentment and envy, the impacts of exposure to positive content on Facebook, the link between envy and depression on Facebook, and the function of tie strength in expecting the emotional results of browsing Facebook. I am specifically interested in how previous research explored the consequences of Facebook use on psychological outcomes, the moderating function of envy in the link between Facebook use and reduced affective wellbeing, the psychological results of non-interactive Facebook conduct, and the role of relationship closeness in anticipating user’s contentment and envy after inspecting a post. A synthesis of the extant literature suggests that inspecting other individuals’ positive news on Facebook brings about contentment through emotional contagion, whereas negative news causes discomfort as a consequence of mood contagion, the transmissible effect being more powerful when the news is associated with a strong tie. The outcomes of this research back the argument that self-confidence and dispositional envy are instrumental in producing Facebook envy. These findings highlight that the emotional results of browsing Facebook are considerably affected by the substance of the comment, the personal attributes of the Facebook user, and link between the reader and the poster. As limitations in the current review, more hypotheses need to be tested and future directions for subsequent multilevel research on the behavioral and cognitive outcomes of Facebook should illuminate why when individuals achieve belongingness demands on Facebook, they feel in a superior way about themselves and their reputation in social circles.